Tyrosine Kinase Inhibitors Are Potent Acute Pulmonary Vasodilators in Rats - Abe, Kohtaro (Am J Respir Cell Mol Biol, 2011)
Tyrosine kinase inhibitors are promising for the treatment of severe pulmonary hypertension. Their therapeutic effects are postulated to be due to inhibition of cell growth–related kinases and attenuation of vascular remodeling. Their potential vasodilatory activities have not been explored. Vasorelaxant effects of the tyrosine kinase inhibitors imatinib, sorafenib, and nilotinib were examined in isolated pulmonary arterial rings from normal and pulmonary hypertensive rats. Phosphorylation of myosin light chain phosphatase and myosin light chain was assessed by Western blots. Acute hemodynamic effects of imatinib were tested in the pulmonary hypertensive rats. In normal pulmonary arteries, imatinib reversed serotonin- and U46619-induced contractions in a concentration-dependent and endothelium-independent manner. Sorafenib and nilotinib relaxed U46619-induced contraction. Imatinib inhibited activation of myosin phosphatase induced by U46619 in normal pulmonary arteries. All three tyrosine kinase inhibitors concentration-dependently and completely reversed the spontaneous contraction of hypertensive pulmonary arterial rings unmasked by inhibition of nitric oxide synthase. Acute intravenous administration of imatinib reduced high right ventricular systolic pressure in pulmonary hypertensive rats, with little effect on left ventricular systolic pressure and cardiac output. We conclude that tyrosine kinase inhibitors have potent pulmonary vasodilatory activity, which could contribute to their long-term beneficial effect against pulmonary hypertension. Vascular smooth muscle relaxation mediated via activation of myosin light chain phosphatase (Ca(2+) desensitization) appears to play a role in the imatinib-induced pulmonary vasodilation.